Respuesta :
The answer is
y= - x-9/3 I believe.
1- Subtract 9 from both sides.
-3y = x - 9
2- Divide both sides by -3
y = - x-9/3
y= - x-9/3 I believe.
1- Subtract 9 from both sides.
-3y = x - 9
2- Divide both sides by -3
y = - x-9/3
Simplifying
9 + -3y = x
9 + -3y = x
9 + -9 + -3y = -9 + x
9 + -9 = 0 0 + -3y = -9 + x -3y = -9 + x
'-3' y=-3 + -0.3333333333x
i hope this helped you out!
9 + -3y = x
9 + -9 + -3y = -9 + x
9 + -9 = 0 0 + -3y = -9 + x -3y = -9 + x
'-3' y=-3 + -0.3333333333x
i hope this helped you out!